The Handbook of Professionally Managed Assets A Definitive Guide to Profiting from Pooled Investments - Fevurly, Keith R. (Apress : Imprint: Apress, 2013)
This practical guide provides a comprehensive overview of professionally managed assets, or investments in which all portfolio decisions and rebalancing are delegated to a fund manager or third-party advice service. Savvy investors looking to achieve a better understanding of the nuances, benefits, and drawbacks of using these products will find the answers they are looking for in The Handbook of Professionally Managed Assets, no matter whether they would like to learn more about mutual funds or hedge funds. There is a considerable lack of knowledge among the investing public about how to properly construct a well-diversified portfolio of investments that includes a selection of professionally managed assets. As a long-standing financial planner, attorney, and educator, Keith Fevurly remedies this issue in The Handbook of Professionally Managed Assets by clearly presenting the major categories of professionally managed assets and revealing the best tactics for investing in these vehicles. Along the way, he reveals each asset's risks and rewards, and he also provides the in-depth knowledge and information investors need to confidently select the right assets for their portfolios. Filled with valuable insights for everyone from financial professionals to individual investors, The Handbook of Professionally Managed Assets stands alone in its ability to shed light on the many investment vehicles that fall under the larger umbrella of professionally managed assets. With topics as wide-ranging as mutual funds, closed-end funds, unit investment trusts, exchange traded funds, hedge funds, managed futures, and more, this invaluable resource will give you the information you need to build a prosperous financial future for yourself and your clients. .